Epidermolysis bullosa in newborn: a case report - Narang, Gursharn Singh; Kumar, Ashwani; Virk, Navneet; Malik, Supriya (International Journal of Contemporary Pediatrics, 2017)
Epidermolysis bullosa is a rare genetic connective tissue disorder. It has many genetic and symptomatic variations but all share the prominent symptom of extremely fragile skin that blisters and tears from minor trauma in the varying degrees of severity and can severely incapacitate the life of the afflicted patient. Treatment still remains a major challenge. Daily wound care, pain management and protective bandaging are the only available treatment options.